Immunosuppressive drugs affect interferon (IFN)-γ and programmed cell death 1 (PD-1) kinetics in patients with newly diagnosed autoimmune hepatitis. (27th March 2017) - Grant, C R; Holder, B S; Liberal, R; Heneghan, M A; Ma, Y; Mieli-Vergani, G; Vergani, D; Longhi, M S
Summary: Autoimmune hepatitis (AIH) is characterized by overwhelming effector immune responses associated with defective regulatory T cells (Tregs ). Several lines of evidence indicate CD4 as the main effectors involved in autoimmune liver damage. Herein we investigate the in-vitro effects of prednisolone, 6-mercaptopurine, cyclosporin, tacrolimus, mycophenolic acid (MPA) and rapamycin, immunosuppressive drugs (ISDs) used in AIH treatment, on the expression of proinflammatory cytokines, co-inhibitory molecules and ability to proliferate of CD4 + CD25 – cells, isolated from the peripheral blood of treatment-naive patients with AIH. We note that in healthy subjects (HS) following polyclonal stimulation and in the absence of ISDs, the expression of interferon (IFN)-γ, interleukin (IL)-17 and tumour necrosis factor (TNF)-α by CD4 effectors peaks at 48 h and decreases at 96 h to reach baseline levels. In contrast, in AIH the expression of all these proinflammatory cytokines continue rising between 48 and 96 h. Levels of programmed cell death-1 (PD-1), T cell immunoglobulin and mucin domain-containing molecule-3 (TIM-3) and cytotoxic T lymphocyte antigen-4 (CTLA-4) increase over 96-h culture both in HS and AIH, although with faster kinetics in the latter. Exposure to ISDs contains IFN-γ and PD-1 expression in AIH, where control over CD4 + CD25 – cell proliferation is also noted upon exposure to MPA. Treatment with tacrolimus and cyclosporin render CD4 + CD25 – cells more susceptible to Treg control. Collectively, our data indicate that in treatment-naive patients with AIH, all ISDs restrain T helper type 1 (Th1) cells and modulate PD-1 expression. Furthermore, they suggest that tacrolimus and cyclosporin may ameliorate effector cell responsiveness to Tregs . Graphical Abstract: